POSITION OF TALENT MANAGEMENT IN CONTEXT OFORGANIZATIONAL FUNCTIONS - Robert Štefko; Ladislav Sojka (European Scientific Journal, ESJ, 2014)
This paper deals with problem of talent management position t within set of organizational methods a management tools. As the problem of talent management is new , there are many problems with terminology and justification of talent management in context of others management tools , especially in relation to human resource management. Paper presents definitions of relevant terms concerned talent management, relation of talent management to human resource management, and stresses specific role of talent management in gaining of competitive position and presents important tools of talent management. Created is model of talent management with a description of important components of talent.